2009
DOI: 10.1007/s10529-009-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of recombinant bone morphogenetic proteins for bone regeneration and repair. Part A: Current challenges in BMP delivery

Abstract: Recombinant human bone morphogenetic proteins (rhBMPs) have been extensively investigated for developing therapeutic strategies aimed at the restoration and treatment of orthopaedic as well as craniofacial conditions. In this first part of the review, we discuss the rationale for the necessary use of carrier systems to deliver rhBMP-2 and rhBMP-7 to sites of bone tissue regeneration and repair. General requirements for growth factor delivery systems emphasizing the distinction between localized and release-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
220
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(226 citation statements)
references
References 49 publications
2
220
0
Order By: Relevance
“…[16][17][18] Some documents have shown that BMP4 exacerbates exaggeratin cardiac I/R injury. 19 In addition, BMP4 is a proinflammatory gene that induces endothelium dysfunction, mediating abnormal expression of endothelial nitric oxide synthase (eNOS) and leads to impairment of vascular relaxation, 20 and that activates NADPH oxidase to induce ROS production and then improves the expression of cyclooxygenase-2 (COX-2) through p38 mitogen-activated protein kinase (p38MAPK).…”
mentioning
confidence: 99%
“…[16][17][18] Some documents have shown that BMP4 exacerbates exaggeratin cardiac I/R injury. 19 In addition, BMP4 is a proinflammatory gene that induces endothelium dysfunction, mediating abnormal expression of endothelial nitric oxide synthase (eNOS) and leads to impairment of vascular relaxation, 20 and that activates NADPH oxidase to induce ROS production and then improves the expression of cyclooxygenase-2 (COX-2) through p38 mitogen-activated protein kinase (p38MAPK).…”
mentioning
confidence: 99%
“…165 Moreover, different anatomical sites require therapeutic doses depending on degree of vascularization, defect size, and number of resident cells. 325 Therefore, appropriate carrier systems are critical for the delivery, retention, and release of GFs at the implanted site to achieve the desired effect. 68,326 Despite the differences in the use of scaffold carriers, GFs dosages and combinations, animal models, and consequently the tissue regeneration outcomes, the potential of GF therapy are undeniable.…”
Section: From Single To Multiple Bioactive Factor Delivery For Skeletmentioning
confidence: 99%
“…The efficacy of rhBMPs will depend on the carrier system that is used to ensure an effective delivery of adequate protein concentrations to the desired site [11,20]. The PTD delivery system has various advantages, including high efficiency in vivo, low toxicity, and controllability of administration, compared with other methods such as viral vector-mediated gene delivery and liposomal delivery [23].…”
Section: Determination Of Rhbmp2/7-ptd Expression Levelsmentioning
confidence: 99%
“…However, the precise cellular and molecular mechanisms of BMPs are not fully understood and require further investigation [8,11].…”
Section: Determination Of Rhbmp2/7-ptd Expression Levelsmentioning
confidence: 99%